ANALISIS KINERJA GEOMETRIK IMPELLER POMPA SENTRIFUGAL BERBASIS PERANGKAT LUNAK - Darto Darto; I Made Sunada (TRANSMISI, 2016)
On the centrifugal impeller is a part that converts the mechanical energy (energy in the blades of the impeller) is passed on to the pump power and efficiency as a result of (their fluid friction losses) due to changes in the flow direction of the blades of the impeller. To obtain performance centrifugal pump impeller, so it needed a thorough analysis, one of which is the analytic geometry. To speed up the process and analytical results are accurate then use the software. In this analysis used software Turbo CF 9.2.8. In this analysis used primary data in the form of geometric parameters of centrifugal pumpa as an input to the software used. The conclusions in the can are the theoretical performance data from the pump impeller type can be generated quickly and accurately.